Research on the impact mechanism and spatial spillover effects of digital infrastructure on urban land green use efficiency: evidence from the Yangtze River Delta region - Tong, Linjie; Tan, Xin; Jin, Yongbo (Frontiers in Environmental Science, 2026)
Digital infrastructure is increasingly recognized as a pivotal driver of green and sustainable urban development. This study examines its impact on the spatiotemporal evolution of Urban Land Green Use Efficiency (ULGUE), focusing on the underlying mechanisms and spatial spillover effects.Utilizing panel data from 41 cities in China’s Yangtze River Delta region(YRD) from 2013 to 2022, we employed a multi-period Difference-in-Differences (DID) framework. The “Broadband China” demonstration program served as a quasi-natural experiment. Robustness was assessed through parallel trend tests, Propensity Score Matching-DID (PSM-DID), and policy exclusion checks. Mechanisms were explored via mediation analysis, and spatial effects were analyzed using a Spatial Durbin Model. The analysis reveals that: (1) Digital infrastructure significantly enhances ULGUE, a finding robust across various sensitivity checks. (2) It indirectly improves ULGUE by promoting industrial upgrading and strengthening local governmental environmental awareness. (3) Spatial heterogeneity is notable: the effect is strongest in Anhui Province, slightly inhibitory in parts of Jiangsu Province, and statistically insignificant in Zhejiang Province and Shanghai. (4) Significant positive spatial spillover effects exist, indicating that digital infrastructure benefits both local and neighboring regions’ green land-use efficiency.These findings underscore the multifaceted role of digital infrastructure in advancing sustainable urban land management. They provide theoretical and empirical insights into pathways for low-carbon urban development and offer policy implications for fostering high-quality, regionally coordinated growth in the YRD region.